1D Josephson quantum interference grids: diffraction patterns and dynamics. (11th January 2016) - Lucci, M; Badoni, D; Corato, V; Merlo, V; Ottaviani, I; Salina, G; Cirillo, M; Ustinov, A V; Winkler, D
Abstract: We investigate the magnetic response of transmission lines with embedded Josephson junctions and thus generating a 1D underdamped array. The measured multi-junction interference patterns are compared with the theoretical predictions for Josephson supercurrent modulations when an external magnetic field couples both to the inter-junction loops and to the junctions themselves. The results provide a striking example of the analogy between Josephson phase modulation and 1D optical diffraction grid. The Fiske resonances in the current-voltage characteristics with voltage spacing, where L is the total physical length of the array, the magnetic flux quantum and the speed of light in the transmission line, demonstrate that the discrete line supports stable dynamic patterns generated by the ac Josephson effect interacting with the cavity modes of the line.